Mika Rottenberg - Easypieces - Norton, Margot ca. 20./21. Jh (New Museum, 2019)
Easypieces' is published for the first New York museum solo presentation of work by Argentine artist Mika Rottenberg (born 1976). Employing absurdist satire to address the critical issues of our time, Rottenberg creates videos and installations that offer subversive allegories for contemporary life. Contributors include Samantha Frost, Associate Professor of Political Science and Gender and Women's Studies at the University of Illinois, Urbana-Champaign; Diana Coole, Professor of Political and Social Theory at the School of Politics of Sociology, Birkbeck, University of London; and Julia Bryan-Wilson, Professor of History of Art at the University of California, Berkeley, in an interview with Rottenberg. The catalog also features an overview by New Museum Curator Margot Norton. 'Easypieces' is part of an ongoing series of solo exhibitions that provide a focused exploration of artists' practices and continues the New Museum's history of giving contemporary artists their first museum presentations in New York. Exhibition: New Museum, New York, USA (26.06.-22.09.2019)
On the occasion of the exhibition "Mika Rottenberg: Easypieces" June 26-September 15, 2019"--Colophon
Keywords: Rottenberg, Mika -- 1976-; Rottenberg, Mika / 1976- / Exhibitions; Rottenberg, Mika / 1976-; Exhibition catalogs; Bildband; Ausstellungskatalog -- New Museum of Contemporary Art -- 26.06.2019-15.09.2019 -- New York, NY